LSPR enhanced gasoline sensing with a U-bent optical fiber. (11th July 2016) - Paul, D; Dutta, S; Biswas, R
Abstract: We report here a gasoline sensor utilizing localized surface plasmon resonance (LSPR) phenomenon of metal nanoparticles (NPs) with a U-bent optical fiber. The optical response of the noble metal NPs upon interaction with gasoline has been simulated and experimentally demonstrated. The increase in gasoline vapor over a period of time induces a change in the refractive index of the adjacent medium of nanoparticle colloids, adhering to the probe, and thus the variation has been observed accordingly. This change in the refractive index in the close proximity to noble metals NPs produces a measurable variation in the output signal that has been correlated with the increase in the concentration of gasoline. The sensor provides better sensitivity corresponding to AgNPs when compared to AuNPs. However, in terms of stability, AuNPs-based LSPR performs better than the AgNPs-based plasmonic response. The present sensing set-up offers a light weight, robust and easy to implement platform that has potent application in detecting volatile liquids very effectively.